The different returns to cognitive ability in the labor and capital markets - Spencer Bastani; Kristina Karlsson; Daniel Waldenström (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
We investigate the returns to cognitive ability in the labor and capital markets. Using population-wide Swedish military enlistment data and administrative tax records, we find that cognitive ability is much better at predicting capital income than labor earnings. The difference is almost a factor of three and remains substantial even after controlling for education, occupation, savings, inheritance, and parental background. Moreover, ability is significantly positively correlated with wealth returns. Our results provide new insights into why inequality in capital income is greater than in labor income and shed light on the drivers of economic mobility.
Keywords: J24; D31; H20; 330; Ability; Skills; Education; Capital income; Wealth